2021
DOI: 10.1111/jfpp.15068
|View full text |Cite
|
Sign up to set email alerts
|

Influence of macro‐perforated polyethylene terephthalate and low‐density polyethylene packaging films on quality and storability of strawberries

Abstract: Perishable nature of strawberry poses serious challenges in maintaining quality and extending its market life. In this study, efficacy of macro‐perforated polyethylene terephthalate polyester (PET), low‐density polyethylene (LDPE), and composite film packaging (PET + LDPE) was evaluated to inhibit fungal decay and retain nutritional and organoleptic attributes of strawberries stored at 2 ± 0.5°C. Strawberries packed in LPDE exhibited better moisture retention, least fungal infection, and delayed loss of membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Similar findings regarding the effectiveness of controlled atmosphere treatments in reducing MDA contents as well as attenuating postharvest decay in blueberry fruit have been reported elsewhere (Rodriguez & Pablo Zoffoli, 2016). TSS and TA are important attributes in determining strawberry quality (Maryam et al ., 2021). Strawberries packed in active EMAP had the highest overall quality, since they were judged firmer, sweeter than passive EMAP and control group.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings regarding the effectiveness of controlled atmosphere treatments in reducing MDA contents as well as attenuating postharvest decay in blueberry fruit have been reported elsewhere (Rodriguez & Pablo Zoffoli, 2016). TSS and TA are important attributes in determining strawberry quality (Maryam et al ., 2021). Strawberries packed in active EMAP had the highest overall quality, since they were judged firmer, sweeter than passive EMAP and control group.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we conducted an analysis of the levels of soluble protein, soluble sugar, soluble solid, and vitamin C in Passiflora spp. fruits collected on the 7th day after the third spraying, following established protocols [ 43 , 44 , 47 , 48 ]. Each experiment was conducted in triplicate to ensure result reliability.…”
Section: Methodsmentioning
confidence: 99%
“…A limit of 6% is normally accepted for this parameter [5], although other authors reported a maximum acceptable weight loss of 2.5%-3% [40]. In the case of FS, weight loss can be a limiting factor when the fruit is stored in open containers [41], where unacceptable values can be achieved within 2-3 days at ambient temperature. Weight loss can be mitigated by controlling ambient humidity and by applying packaging technology.…”
Section: Physicochemical Qualitymentioning
confidence: 99%
“…Strawberry microbiological quality can also be characterized in terms of total aerobic mesophilic counts, yeast and mould counts and coliforms [57,58]. In ready-to-eat products, these microbiological counts can reflect processing hygienic conditions and have been shown to limit shelf life under certain packaging and storage conditions [41]. In this sense, local regulations play an important role in defining microbiological criteria for readyto-eat products [59,60].…”
Section: Microbiological Qualitymentioning
confidence: 99%